THE EFFECT OF APPLYING THINK-TALK-WRITE STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Indah Pratiwi; Lince Sihombing (Universitas Negeri Medan, 2015)
This study is an attempt to discover the effect of applying Think-Talk-Write strategy on students’ achievement in writing descriptive text. The objective of this study were to find out whether applying Think-Talk-Write strategy affect the students’ achievement in writing descriptive text. This study was an experimental research. In conducting the research, the writer used 60 students of Al-Fattah Senior High School Medan as the sample. The 60 students were taken from two classes and they were divided into two groups namely the experimental group who was taught by using Think-Talk-Write strategy and the control group who was taught without Think-Talk-Write strategy. The data of the test were collected by administering written test. The data were analyzed by using t-test formula. The result of the analysis shows that the value of t-observed is higher than the value of t-table (2,3> 2,00 (α = 0.05)) with the degree of freedom (df) = N-2 = 58. It means that there is significant effect of applying Think-Talk-Write strategy on students’ achievement in writing descriptive text. So the alternative hypothesis (Ha) is accepted. The conclusion is that applying Think-Talk-Write strategy can encourage and increase the students’ achievement in writing descriptive text. Therefore, it is suggested that English teacher should try to apply this strategy.